Peningkatan Kualitas Keripik Jamur Tiram Produksi Kelompok Tani Pesona Jamur dengan Mesin Spinner - Venditias Yudha; Nur Hayati; Satriawan Dini Hariyanto (Institut Pertanian Bogor, 2022)
Pesona Jamur farmer groups primarily focus on producing baglog and cultivating oyster mushrooms. Currently, they are doing business development by making a food product called oyster mushroom chips. This program aims at improving the quality of processed oyster mushroom chips by applying the appropriate technology of a spinner machine equipped with a magnetic contactor. The method used were practical training and assistance in processing oyster mushroom chips then dissemination of applied technology a spinner machine to the partners. The result of this program indicated that the oyster mushroom chip product processed by the Pesona Mushroom Farmers Group has a light brown color and the shape of the mushroom chips is not crushed. Oyster mushroom chip products are of higher quality than before the training activities because they had used the correct processing technique. The taste of the chips is also more savory, coupled with the complete form of chips, which are expected to attract consumers and increase product value. The correct chip processing technique and a spinner machine can minimize the oil content in oyster mushroom chips and expired dates. The product's expiration has increased from one month to four months without preservatives.